Development of skills in children with ASD using a robotic platform - Silva, Sara Isabel Azevedo da (2012)
The interaction and communication skills are essential to live in society. However, individuals with autism spectrum disorders (ASD) have a gap in these abilities which affects their daily life. Previous studies suggest that children with ASD demonstrate some positive behaviors in presence of a robotic platform. This study intends to evaluate the effect of a robotic platform on children with ASD, checking if the platform can be a stimulating agent for children's interaction, as well as a skill learning promoter. So, it is used the robot Lego Mindstorms NXT as a mediator/reward to encourage children with ASD to interact with others and also to learn some cognitive skills.